Pembaruan Hukum Perwakafan di Indonesia - Ibrahim Siregar (Universitas Darussalam Gontor, 2012)
This article concentrates on Islamic law product relating to charitable religious endowment (waqf) in Indonesia. Based on the traditional perspective of fiqh originated from the earlier Islamic jurists of orthodox view and in turn it had long been legislised as part of Indonesia positive law system, the law of waqfhad regulated that the wealth to be waqf shall be limited to only unmoving properties. This regulation had led the management of waqf to be unproductive to raise the social welfare.By the virtue of the relatively wider viwpoint of the contemporar y Islamic law thinkers,the Islamic law refor m takes place in Indonesia particularly at the level of postive law ,namely Law Number 41/2004 Relating to Waqf. This law stipulates the thing to be waqf could be either unmoving or moving properties, like cash, gold, certificate of obligation, inteletual wealth, and so forth. This law also lays down the regulation relating to the penalty against those who deviate in managing a waqf. However, as a critque and recommendation the writer propose that the society could be involved in preser ving the purpose of a waqf which is the right of Allah. And it could be conducted by stipulating the class action as a way of the settlements of dispute occuring to a waqf property.